Environmental management strategy for coastal waters through a dynamic system approach in Tanjungpinang City region, Riau Islands, Indonesia - Febrianti Lestari (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
Coastal and small islands are faced with various significant challenges, one of which is the vulnerability to contamination by waste disposal from land and the magnitude of the impact it has on coastal waters. This study presents a framework for formulating environmental management of small island coastal waters from anthropogenic sources of terrestrial land with a system dynamic approach based on the characteristics of physical environmental factors and oceanography of the waters. The purpose of this research is to formulate a strategy for environmental management of the coastal waters of Tanjungpinang City. The results showed that the total magnitude of the waste load originating from anthropogenic sources on the mainland of Tanjungpinang City was 1,073.98 tons/year. The burden of organic waste in Tanjungpinang City is identified from five sources, namely domestic waste from residential areas, hotel and restaurant waste, the food industry, and the agricultural and livestock sectors. The Tanjungpinang coastal waters environmental management strategy with a dynamic system approach is recommended to use an optimistic scenario, but it needs to be supported by several policies in the form of (1) government support to build a community wastewater treatment facility or communal WWTP, (2) increasing community participation and concern for the aquatic environment , and (3) preparing regional strategic plans, specifically in the field of aquatic environmental management in the context of controlling effluent in coastal waters of small islands.